2005
DOI: 10.1590/s0103-50532005000400028
|View full text |Cite
|
Sign up to set email alerts
|

Long-range correlations ( n j C,H n > 3 ) in the HMBC spectra of 3-(4-oxo-4H-chromen-3-YL)-acrylic acid ethyl esters

Abstract: Um estudo sistemático das correlações de longo alcance em espectros de HMBC foi feito para uma série de ésteres etílicos do ácido cis-e trans-3-(4-oxo-4H-chromen-3-il) acrílico e os derivados 5-hydroxilados. Os resultados foram comparados com os já observados para espectros IMPEACH-MBC e CIGAR-HMBC. Um acoplamento incomum do tipo A systematic study about the long-range correlations observed in the HMBC spectra of a series of cis and trans 3-(4-oxo-4H-chromen-3-yl)-acrylic acid ethyl esters, and 5-hydroxy deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The E/Z product mixture has a 55/40 E/Z ratio and an overall yield of 95% [16]. When N-vinylpyrrolidinone, a dienophile already used in inverse electron demand Diels-Alder reactions [17], reacted with 1 in toluene at 140 • C in a sealed tube, a mixture of isomeric tetracyclic compounds 5 and 6, along with the xanthone 2, were obtained in yields of 35%, 15% and 2%, respectively (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…The E/Z product mixture has a 55/40 E/Z ratio and an overall yield of 95% [16]. When N-vinylpyrrolidinone, a dienophile already used in inverse electron demand Diels-Alder reactions [17], reacted with 1 in toluene at 140 • C in a sealed tube, a mixture of isomeric tetracyclic compounds 5 and 6, along with the xanthone 2, were obtained in yields of 35%, 15% and 2%, respectively (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…The starting chromones 3, 11-13 were obtained by Wittig reactions of parent 3-formylchromone (7) and its 5-hydroxy-derivative (8) with carboethoxymethylenetriphenylphosphorane (9) or triphenylphosphoranylidenacetonitrile (10). The E/Z product mixtures were obtained with good overall yields and variable E/Z ratios (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Oxo-4H-chromen-3-yl)acrylic acid ethyl ester (E-3) 10. Yield 50 %, crystallized from EtOAc/hexane as colorless needles.…”
mentioning
confidence: 99%
“…1 H NMR (300 MHz, CDCl 3 ): 7.52 (ddd, 1H, J 1 = 7.9 Hz, J 2 = 7.2 Hz, J 3 = 1.1 Hz, 6-H), 7.56 (dd, 1H, J 1 = 8.5 Hz, J 2 = 1.1 Hz, 8-H), 7.77 (ddd, 1H, J 1 = 8.5 Hz, J 2 = 7.2 Hz, J 3 = 1.7 Hz, 7-H), 8.32 (dd, 1H, J 1 = 7.9 Hz, J 2 = 1.7 Hz, 5-H), 8.57 (s, 1H, 2-H), 10.40 (s, 1H, CHO). 3-(4-oxo-4H-chromen-3-yl)acrylate (4) [16,17] MP: 111.5-112.5ºC.…”
Section: -Formyl-4[h]-1-benzopyran-4-one (1) [8]mentioning
confidence: 99%
“…Generally, the IC 50 for oxygen uptake inhibition is about one order of magnitude greater than the IC 50 for cytotoxicity. In relation to these compounds, spectroscopic and reactivity studies of chromone 4 have also been reported [16,17].…”
Section: No 4 519 -524mentioning
confidence: 99%